Study on Effects of Wheatgrass (Triticum aestivum) Juice on Serum Triglyceride of Experimentally Induced Hypercholesterolaemic Male Long Evans Rat - Afroz, Rokhsana Dil; Nurunnabi, Abu Sadat Mohammad; Hossain, Mohammad Zaid; Khan, Md. Ismail; Parvin, Shamima; Rahman, Hasanur (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 197-203 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15358